Analisis Pengaruh Return On Assets (ROA) dan Return On Equity (ROE) Terhadap Efisiensi Biaya Operasional PT Indo Sukses Logistik Jakarta Periode 2021-2023 - Wulan Afifa (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the influence of Return on Assets and Return on Equity on operational cost efficiency at PT Indo Sukses Logistik Jakarta during the 2021–2023 period. The background of this research is based on the importance of operational efficiency in the logistics industry, where optimal cost management greatly determines the competitiveness and sustainability of the company.The research employs a quantitative approach with descriptive and verificative methods. The data used are secondary data in the form of the company’s monthly financial statements. The independent variables in this study are ROA and ROE, while the dependent variable is operational cost efficiency, measured by the ratio of operational costs to revenue.The results indicate that partially, ROA has no significant effect on operational cost efficiency, and ROE also has no significant effect when tested independently. However, simultaneously, ROA and ROE have a significant effect on operational cost efficiency. These findings suggest that improving the effectiveness in asset utilization can contribute to better cost efficiency.It is concluded that the company should enhance its asset management efficiency in order to improve profitability and reduce operational expenses.